Bioenergy Power Generation Improved Through Biomass Co-Firing - Cantika Setya Permatasari Setya; Johan Fahrizki; Nugroho Adi Sasongko (Indonesian Life Cycle Assessment Network (ILCAN), 2019)
Generally, power plants have an environmental negative impact, due to emissions released from the power plant process. The Coal-fired power plant is the most dominant in the world. This is due to the relatively cheap price of coal and high calories produced. But on the other hand emissions generated by coal-fired power plants are quite large compared to other types of power plants, while all countries are working to reduce global warming, one of which is by reducing CO2 emissions. Utilization Renewable Energy is one of the solutions in efforts to reduce the use of fossil energy so that there is a decrease in CO2. Biomass is renewable energy which is currently widely used as fuel for electricity generation, Biomass fuel can be used 100% for a plant called PLTBm and can also be a coal-fired power plant with a certain percentage mix. Therefore, an analysis using the Life Cycle Assessment (LCA) method is used to determine differences in emissions produced between coal-fired power plants compared to the Biomass co-firing system. The result is a PLTU with a Biomass co-firing system produces lower emissions than a 100% coal-fired power plant.